2019
DOI: 10.1016/j.bone.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Aging of mouse intervertebral disc and association with back pain

Abstract: With the increased burden of low back pain (LBP) in our globally aging population there is a need to develop preclinical models of LBP that capture clinically relevant features of physiological aging, degeneration, and disability. Here we assess the validity of using a mouse model system for age-related LBP by characterizing aging mice for features of intervertebral disc (IVD) degeneration, molecular markers of peripheral sensitization, and behavioral signs of pain. Compared to three-month-old and one-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 105 publications
9
83
0
Order By: Relevance
“…Additionally, recent evidence of innervation in discogenic neck pain supports a similar mechanism for discogenic LBP . Induced and age‐related disc degeneration in mouse and rat models have also exhibited increased disc innervation, including into the NP . These data demonstrate a strong link between disc degeneration, increased disc innervation, and discogenic pain.…”
mentioning
confidence: 66%
“…Additionally, recent evidence of innervation in discogenic neck pain supports a similar mechanism for discogenic LBP . Induced and age‐related disc degeneration in mouse and rat models have also exhibited increased disc innervation, including into the NP . These data demonstrate a strong link between disc degeneration, increased disc innervation, and discogenic pain.…”
mentioning
confidence: 66%
“…The intrinsic intra-and interanimal variation in disc degeneration phenotypes of lumbar and caudal discs at 6 month and 1 year was noted and is shown in Supplemental Figure 2. Indeed, genetic interactions with environmental stimuli have been indicated to substantially differ between lumbar levels in twin studies, and the biomechanical environment has been shown to differ significantly level by level along the spinal column, resulting in level-specific phenotypic outcomes (30,(39)(40)(41)(42). Although it is plausible that the phenotypic variability between animals was caused by some variation in recombination efficiencies of the floxed allele, the overall recombination is high, regardless of the spinal level.…”
Section: Resultsmentioning
confidence: 99%
“…Significance between collagen fiber distributions was determined by χ 2 test. Since the unique interactions between genetic, biological, and biomechanical factors at individual spinal levels have been shown to produce different phenotypic outcomes, each disc was considered as an independent sample (30,(40)(41)(42). All statistical analyses were done using Prism 7 (GraphPad Software).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, recent studies demonstrated that mice fed a high-fat diet for 8 weeks showed increased time immobile in tail suspension, interpreted as a characteristic of depression-like behavior (56). This behavior is in contrast to both genetic and age-related mouse models of IVD degeneration and axial pain which show increased time rearing in tail suspension (57,58). This confounding factor may impact the outcome of tail suspension in the diet-induced obesity model, and consequently the interpretation of our ndings.…”
Section: Discussionmentioning
confidence: 99%